The public international law of trade in legal services - Collins, David, 1975- (Cambridge international trade and economic law., 2019)
This book examines the international legal regime covering trade in legal services. While legal services are a vital component of the economies of many developed and emerging countries, they remain poorly liberalized with numerous restrictions undermining market access for foreign suppliers. Although some modern bilateral and regional trade agreements have begun to address barriers to trade in legal services, few go beyond the basic commitments of non-discrimination and transparency contained in the WTO GATS. This book approaches the pressing need to open the global market for trade in legal services across the four modes of supply: cross border, consumption abroad, commercial presence and temporary movement of natural persons. It considers changes under way within the legal profession brought about by alternative business structures and technology. Both underscore the importance of reconceptualizing trade in legal services as one that should be as open as possible with a view to maximizing competition while safeguarding the needs of clients.